Towards the Theory of Politics (About the Concept, Meaning and Metamorphoses of Politics) - Yankov, Georgi (UNWE Yearbook, 2011)
On the basis of analysis of different interpretations and definitions of the term politics, the author concludes: It is equally legitimate to define politics as allocation of power and values, as state government, as management of the public sphere (creating rules for the public sphere functioning), as activity related to public (social) affairs and achieving the „general welfare“, as management of inequalities in the society, as relations of solidarity and contradictions of social groups, as conflict relations (conflict solutions), as transformation of the private interest in public…The study answers the following questions: who is the main issue of politics; how do politics and moral unite; what is the subordination between politics and law. This dependence is bipartite: on one side, politics in certain respect is practical realization of legal norms, on other, the legal system is built on decisions taken by the political legislator, therefore explaining the „instrumental character of law“ (Jurgen Habermas). So law is situated between the politics and moral.A special attention is drawn to the functions of the vocational politician and statesman, as well as to the politics metamorphoses in the beginning of XXI century. The paper substantiates the idea for reconstruction of public power and state, for „recreation of state“ (J. Stieglitz). The study finishes with the historical evolution of political science as academic discipline and science, having an object for study politics, power and state government.